Where is the xenon that is missing from the Earth's atmosphere? - Ortega San Martin, Luis (2012)
The chemical analysis of the meteorites considered to resemble closely the primordial matter which led to the formation of the Earth indicates that the concentration of xenon gas in our atmosphere is lower than expected. It seems that this deficiency is related to the noble gases’ solubility in the oxygen vacancies present in the perovskite structure of magnesium silicate, MgSiO3, the main constituent of the Earth’s mantle.